Does there exist passive voice in Lakhota and Cheyenne? - Avelino Corral Esteban (Revista de Lingüística y Lenguas Aplicadas)
This article attempts to provide conclusive evidence to decide on the existence or absence of passive in two Native American languages, namely Lakhota and Cheyenne, which exhibit a similar behaviour in this respect. Given that it is evident that these two languages do not show examples of an English-style passive, that is, considering the concept of “passive” from the viewpoint of traditional grammar, it will be necessary to study this issue from a different angle, presented in this case by the Role and Reference Grammar (hereafter RRG) (Van Valin and LaPolla, 1997). Thanks to its marked typological orientation, this theoretical framework makes it possible to see both the similarities and differences between these languages, as well as to solve the problems that arise when studying their grammar owing to their morphological complexity. With respect to grammatical voice, it is crucial to analyze these two languages typologically in terms of the morpho-syntactic parameter denominated “referential structure”´. This analysis will shed light on this issue by showing that there are two different types of languages with respect to this parameter and that this distinction has a bearing on the existence of two different types of passive, whose combination will be exhibited by the English-style passive.